Factors affecting fertility desires in the Philippines - David, Clarissa C.; Atun, Jenna Mae L. (2014)
Factors affecting fertility desires in the Philippines were examined using data from a national survey and from individual and group qualitative interviews involving 143 respondents. Fertility goals usually range from two to three children, but evidence suggests that they are dynamic and may change over a person’s lifetime. Qualitative interviews reveal that when negotiating about family size, it is the partner who wants more children that will be followed. A strong demand for gender balance among offspring creates a willingness to have more children than originally desired. Fertility goals increase over time among women. While those who start childbirth at a very young age successfully space their children, they tend to want larger families than those who start late. Initial fertility goals among women are generally low but may increase because of higher fertility desires among men, a demand for gender balance in children, and the desire for babies once their children have grown.
Keywords: Parental preferences for sex of children; Human fertility; Family size -- Statistics; Contraceptives; Family planning